Knowledge Transfer For The Implementation Of The New CAP And The Guidelines Of The European Green Agreement - A Measure From The Strategic Plan "From Farm To Fork" For A Fair, Healthy And Environmentally Friendly Food System With Applicability In The Mountain Area - Carmen CĂTUNĂ-BOCA; Gabriel POPESCU; Radu-Gheorghe ANTOHE (Communications of International Proceedings, 2021)
The mountains of Romania are a defined geographical, economic and social entity, with relief, climate, natural and socio-cultural heritage, identity recognized in Europe and in the world. Mountain areas are ecologically fragile areas, which need support for protection, development and specific management, determined by the right of difference, recognized at European and global level, being a common heritage, with value, which must be recognized by all and preserved. The main resources of Romania's mountains are represented by the forest fund and biodiversity, the forage flora of the natural meadows, mineral waters, landscapes and the local anthropic factor, bearer of economic and cultural traditions, determinant for the development of resources. The major objective of the paper is the implementation of the new strategic guidelines of the European Green Agreement, the development of the short supply chain, production and marketing of products in the mountain area to ensure the market for mountain products. Developing environmentally friendly actions, encouraging all actors in the entire short chain to reduce environmental pollution and food waste, to achieve a sustainable food system.
Keywords: Mountain Area; Common Agricultural Policy; Sustainable Development; Farm; Mountain Product; Consumer; Biodiversity